Neonatal mortality and coverage of essential newborn interventions 2010 - 2013: a prospective, population-based study from low-middle income countries. Issue 2 (December 2015) - Dhaded, Sangappa; Somannavar, Manjunath; Vernekar, Sunil; Goudar, Shivaprasad; Mwenche, Musaku; Derman, Richard; Moore, Janet; Patel, Archana; Pasha, Omrana; Esamai, Fabian; Garces, Ana; Althabe, Fernando; et al.
Abstract Background Approximately 3 million neonatal deaths occur each year worldwide. Simple interventions have been tested and found to be effective in reducing the neonatal mortality. In order to effectively implement public health interventions, it is important to know the rates of neonatal mortality and understand the contributing risk factors. Hence, this prospective, population-based, observational study was carried out to inform these needs. Methods The Global Network's Maternal Newborn Health Registry was initiated in the seven sites in 2008. Registry administrators (RAs) attempt to identify and enroll all eligible women by 20 weeks gestation and collect basic health data, and outcomes after delivery and at 6 weeks post-partum. All study data were collected, reviewed, and edited by staff at each study site. The study was reviewed and approved by each sites' ethics review committee. Results Overall, the 7-day neonatal mortality rate (NMR) was 20.6 per 1000 live births and the 28-day NMR was 25.7 per 1000 live births. Higher neonatal mortality was associated with maternal age > 35 and <20 years relative to women 20-35 years of age. Preterm births were at increased risk of both early and 28-day neonatal mortality (RR 8.1, 95% CI 7.5-8.8 and 7.5, 95% CI 6.9-8.1) compared to term as were those with low birth weight (<2500g). Neonatal resuscitation rates were 4.8% for hospital deliveries compared to 0.9% for home births. In the hospital, 26.5% of deliveries were by cesarean section with an overall cesarean section rate of 12.5%. Neonatal mortality rates were highest in the Pakistan site and lowest in Argentina. Conclusions Using prospectively collected data with high follow up rates (99%), we documented characteristics associated with neonatal mortality. Low birth weight and prematurity are among the strongest predictors of neonatal mortality. Other risk factors for neonatal deaths included male gender, multiple gestation and major congenital anomalies. Breech presentation/transverse lie, and no antenatal care were also significant risk factors for neonatal death. Coverage of interventions varied by setting of delivery, with the overall population rate of most evidence-based interventions low. This study informs about risk factors for neonatal mortality which can serve to design strategies/interventions to reduce risk of neonatal mortality. Trial registration The trial is registered at clinicaltrials.gov. ClinicalTrial.gov Trial Registration: NCT01073475